Beyond the third dimension of BIM: A systematic review of literature and assessment of professional views. (September 2018) - Charef, Rabia; Alaka, Hafiz; Emmitt, Stephen
Abstract: Across the world, the use of Building Information Modelling (BIM) and the three-dimensional (3D) model in projects are increasingly frequent for supporting design tasks. The digital data embodied in the BIM model is shared between the project stakeholders from the various disciplines. After giving an overview of the BIM 3D Model data used for planning (4D) and costing (5D), the study assesses the level of clarity or confusion on what the numbers of dimension refer to after the 5th dimension. A systematic review of the different BIM dimensions was conducted associated with an online questionnaire sent to various Architecture, Engineering and Construction stakeholders across Europe. The online questionnaire survey was limited to the 28 European Union (EU) countries. Each of the 28 EU countries was represented by at least one respondent. The research identified 52 papers considering BIM 4D Model, 15 considering 5D modelling, 6 considering the 6D Model and 2 considering the 7D. It was also identified a confusion between academics and practitioners for the 6D and 7D BIM dimensions. In fact, 86% of the professionals, actually using 6D, allocate Sustainability to 6D. Whereas 85% of the professionals using 7D allocate it to Facility Management. Highlights: No current agreement on what BIM dimensions represent beyond the 5th dimension. Neither academics nor practitioners are united in what each dimension best represent. Most common suggestions on what the dimensions should represent are proposed.